2002
DOI: 10.1046/j.1460-9568.2002.02140.x
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine‐induced, suprachiasmatic nucleus‐independent circadian rhythms of activity and mPer gene expression in the striatum of the mouse

Abstract: While the suprachiasmatic nucleus (SCN) coordinates the majority of daily rhythms, some circadian patterns of expression are controlled from outside of the SCN. These include responses to daily methamphetamine (MAP) injection, or daily restricted feeding. The mechanisms underlying these SCN‐independent circadian rhythms are unknown. A circadian oscillation in the expression of mPer1 and/or mPer2, mouse period, in the SCN is considered necessary to generate an SCN‐dependent circadian rhythm. Therefore, in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(101 citation statements)
references
References 34 publications
5
95
1
Order By: Relevance
“…Since SCN is thought to coordinate and regulate behavioral clocks in mammals, only a few studies have explored the SCN-independent rhythms of clock genes in the brain. Similar to our findings, Iijima et al (2002) observed SCN-independent mPer mRNA expression in the mouse striatum.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Since SCN is thought to coordinate and regulate behavioral clocks in mammals, only a few studies have explored the SCN-independent rhythms of clock genes in the brain. Similar to our findings, Iijima et al (2002) observed SCN-independent mPer mRNA expression in the mouse striatum.…”
Section: Discussionsupporting
confidence: 92%
“…Even though all three mPer isoforms cycle at both the mRNA and the protein levels in the SCN, mPer1 also shows region-specific and SCN-independent expression rhythm (von Gall et al, 2001;Sun et al, 1997;Iijima et al, 2002). Since SCN is thought to coordinate and regulate behavioral clocks in mammals, only a few studies have explored the SCN-independent rhythms of clock genes in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…NPAS2 may also function in the place of CLOCK in the SCN if the CLOCK protein is genetically disrupted (Debruyne et al, 2006). Though the central circadian pacemaker is located in the SCN, all of these genes are expressed throughout the brain and in other organs where they function as peripheral clocks that respond to nonphotic stimuli, and likely in other processes unrelated to circadian rhythms (Abe et al, 2001;Stokkan et al, 2001;Iijima et al, 2002;Granados-Fuentes et al, 2006;McDearmon et al, 2006;Mieda et al, 2006).…”
Section: The Molecular Clockmentioning
confidence: 99%
“…Furthermore, circadian gene expression outside of the SCN, in these specific regions, may contribute to their rhythmic activity. Circadian activity rhythms in rodents can be entrained to daytime methamphetamine injections, even in SCN lesioned animals (Iijima et al, 2002). This treatment shifts the expression of the period genes in striatal regions typically associated with movement control, in a manner that matches the shift in activity rhythms (Iijima et al, 2002).…”
Section: Influence Of the Molecular Clock On Mood-related Neurotransmmentioning
confidence: 99%
See 1 more Smart Citation